A Flux Detection Probe to Quantify Dynamic Groundwater‐Surface Water Exchange in the Hyporheic Zone. Issue 6 (13th April 2020) - Thomle, Jonathan; Strickland, Chris; Johnson, Tim C.; Zhu, Yue; Stegen, James
Abstract: A new probe was designed to quantify groundwater‐surface water exchange in the hyporheic zone under dynamic stage condition. Current methods focus on either vertical pore water velocity or Darcy flux measurements. Both parameters must be understood to evaluate residence time and mass flux of constituents. Furthermore, most instruments are not well suited for monitoring instantaneous velocity or flux under dynamic exchange conditions. For this reason, the flux detection probe (FDP) was designed that employs electrogeophysical measurements to estimate in situ sediment porosity, which can be used to convert pore water velocity to Darcy flux. Dynamic pore water velocity is obtained by monitoring fluid conductivity and temperature along the FDP probe. Pressure sensors deployed at the top and bottom of the probe provide the additional information necessary to estimate vertical permeability. This study focuses on the use of a geophysical method to estimate pore water velocity, porosity, and permeability within a controlled soil column where simulated river water displaces simulated groundwater. The difference between probe derived and theoretical pore water velocity using natural tracers such as electrical conductivity and temperature was −4.9 and 3.9% for downward flow and 1.1 and 12.8% for upward flow, respectively. The difference in porosity calculated from mass and volume packed in the soil column and probe measure porosity ranged between −3.2% and 1.5%. Also, the calculated hydraulic conductivity differed from probe derived values by −8.9%. Abstract : Article impact statement : New probe designed to measure GW‐SW interaction parameters such as Darcy's flux, pore water velocity, porosity, and permeability.